Diabetes and Ramadan: Practical guidelines 2021. (March 2022) - Hassanein, Mohamed; Afandi, Bachar; Yakoob Ahmedani, Muhammad; Mohammad Alamoudi, Reem; Alawadi, Fatheya; Bajaj, Harpreet S.; Basit, Abdul; Bennakhi, Abdullah; El Sayed, Adel A.; Hamdy, Osama; Hanif, Wasim; Jabbar, Abdul; et al.
Abstract: Fasting during Ramadan is one of the five pillars of Islam and is obligatory for all healthy Muslims from the age of puberty. Though individuals with some illness and serious medical conditions, including some people with diabetes, can be exempted from fasting, many will fast anyway. It is of paramount importance that people with diabetes that fast are given the appropriate guidance and receive proper care. The International Diabetes Federation (IDF) and Diabetes and Ramadan (DaR) International Alliance have come together to provide a substantial update to the previous guidelines. This update includes key information on fasting during Ramadan with type 1 diabetes, the management of diabetes in people of elderly ages and pregnant women, the effects of Ramadan on one's mental wellbeing, changes to the risk of macrovascular and microvascular complications, and areas of future research. The IDF-DAR Diabetes and Ramadan Practical Guidelines 2021 seek to improve upon the awareness, knowledge and management of diabetes during Ramadan, and to provide real-world recommendations to health professionals and the people with diabetes who choose to fast.